Librarians’ Utilization of Intellectual Property Protection Rights (IPPR) and its Challenges in Public Universities in Southern Nigeria - Eruanga, Charles Ejesei; Omwanghe, James Etinosa (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025DO - 10.58709/niujss.v11i2.2172, 2025)
This study examined Librarians utilization of Intellectual Property Protection Rights (IPPR) in public universities in Southern Nigeria.The mixed method of research techniques was adopted for data collection. A population of 327 was used with complete enumeration. The results showed that there were perceived usefulness of IPPR to librarians (x = 3.26) and challenges of IPPR administration (x= 2.99). The study concluded that Librarian utilization of IPPR is necessary and there is need for proper administration of IPPR which will reduced the rate of piracy and plagiarism towards research activities, allocated time for research productivity in the public universities, sensitization of copyright laws, cooperation of the research teams, sustainability support, provision of research information and authorization for external research play a greater role in enhancing the librarian utilization of IPPR in public universities in Southern Nigeria.